Application of Sacramento river forecast model on an Indian catchment - GOSAIN , A. K.; ABBI, S. D. S. (MAUSAM, 1980)
Sacramento model, which is a conceptual watershed model, has been applied suc-cessfully to the upper Yamuna catchment for runoff simulation at Kalanaur outlet point. The model enables the calculation, in six hourly values, of water transfer (interception, evapotranspiration percolation etc) of the state of different phases of water cycle and of the flow at the outlet of the area (direct runoff, surface runoff, interflow and baseflow). Mathematical functions used in the model formulation in order to represent the physical processes taking place in the catchments, have been described in detail. The physical description of various model parameters and method of their evaluation are also given.